The Conception and Practice of Assessment from the Perspective of Primary Education Teachers in Croatia - Letina, Alena (Sodobna pedagogika, 2025)
This paper presents the results of a study aimed at examining Croatian primary education teachers’ conceptions of assessment and the correlation between these conceptions and the implementation of assessment in their teaching practice. The analysis of teachers’ conceptions includes considerations of the reliability and importance of assessment, its role in fostering students’ development, the perception of assessment as a tool for ensuring the quality of school and teacher performance, and its role in preparing students for examinations. The study also examines teachers’ assessment practices, analyzing whether they predominantly focus on formative assessment thus fostering student development, or on summative assessment by preparing students for test-related tasks. The research was conducted on a sample of 261 primary education teachers in Croatia. The findings reveal a statistically significant correlation between teachers’ perceptions of assessment and its implementation in teaching. Teachers who perceive assessment as important for students’ personal development are more likely to employ formative assessment in their teaching. Based on the results, the study discusses implications for practice and possibilities for improving the perception and implementation of assessment in primary education, emphasizing the potential of assessment to promote holistic student development.
Keywords: cilji ocenjevanje znanja; formative assessment; formativno spremljanje; fostering student development; purpose of assessment; samoocenjevanje učiteljev; spodbujanje razvoja učencev; sumativno ocenjevanje znanja; summative assessment; teacher's self assessment